Amino acid and soluble nitrogen evolution throughout ripening of Serra da Estrela cheese - Tavaria, Freni K. (2010)
Four batches of Serra da Estrela cheese originating from as many dairy farms were sampled throughout the ripening period, and assayed for the evolution of free amino acid (FAA) content, total nitrogen content (TN), water-soluble nitrogen content (WSN), trichloroacetic acid-soluble nitrogen content (TCASN) and phosphotungstic acid-soluble nitrogen content (PTASN). The WSN content increased from 1% (on the day of manufacture) up to 43% of TN by 180 d of ripening, thus reflecting the intense proteolytic activity of the enzymes contributed by the plant coagulant utilized. The TCASN was also found to be high in this cheese by the end of ripening (16–20%), which suggests a high extent of FAA release throughout maturation. The major FAA by 180 d of ripening were Glu, Val, Leu and Lys, representing 56–70% of the total in all four dairies sampled. Cheeses produced from refrigerated milk possessed higher amounts of g-amino-n-butyric acid (Gaba) and lower amounts of Glu when compared with those manufactured withnon-refrigerated milk.